Analytical and Stochastic Modeling Techniques and Applications 18th International Conference, ASMTA 2011, Venice, Italy, June 20-22, 2011. Proceedings - Al-Begain, Khalid; Balsamo, Simonetta; Fiems, Dieter; Marin, Andrea (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 18th International Conference on Analytical and Stochastic Modeling Techniques and Applications, ASMTA 2011, held in Venice, Italyin June 2011. The 24 revised full papers presented were carefully reviewed and selected from many submissions.The papers are organized in topical sections on queueing theory, software and computer systems, statistics and inference, telecommunication networks, and performance and performability.